In search of the humanum: on order and disorder in Kamaldeen Balogun’s Rihlah al-Bahth an al-Insan (2015)
The works of Balogun have often been noted for providing antidotes to social maladies. This is particularly true of his creative work entitled Rihlah al-Bahth, in which notions of order and disorder have been mirrored. The paper, using Jacques Derrida's theory, examines construction and representation of order and disorder and search for the humanism across cultures and civilizations. It gives a vivid picture of the social cankerworms that permeate all facets of establishment such as bribery, reduction in the weight and double standard of morality, practice of prostitution, siphoning public funds, exploitation of tenants by landlords, selfishness of members of National Assembly, etc. The paper concludes these vices, as against author's impression, can still be nipped in the bud, despite the rarity of the righteous ones to champion the cause.